Down hanging sponge system for wastewater treatment - Hau, Han Chuan (2024)
In September 2015, the Sustainable Development Goals (SDGs) were established to address global challenges, including ensuring access to clean water and sanitation (SDG 6). Despite this, water scarcity remains a significant issue worldwide, exacerbated by factors such as population growth and uneven development. The water crisis and pollution in Malaysia, particularly in the state of Selangor, present significant challenges to both urban and rural populations. This study investigated the efficacy of the Down Hanging Sponge (DHS) system as an alternative to conventional wastewater treatment methods in addressing these pressing issues. After existing water crisis scenario and conventional biological wastewater treatment methods were reviewed, the study focused on the design and evaluation of a laboratory-scale DHS-G3 reactor for wastewater treatment. The DHS-G3 reactor designed utilized easily accessible materials such as plastic containers, bioballs, and straws as well as featuring a two-segment design. Notably, the DHS-G3 reactor demonstrated remarkable performance in COD removal efficiency and nitrification efficiency. The reactor exhibited efficient nutrient removal, with COD removal efficiency ranging from 68.84 % to 98.37 % and nitrification efficiency ranging from 16.08 % to 62.71 %. Despite encountering challenges related to limited denitrification activities of 4.44 % to 30.0 %, the DHS-G3 reactor’s performance underscored its potential as a cost-effective and sustainable solution to Malaysia's water treatment challenges, as external aeration systems were not needed. This research highlighted the promise of the DHS system in providing cleaner water for all Malaysians while promoting environmental sustainability.